UTILIZATION PATTERN OF NON-TIMBER FOREST PRODUCTS BY RURAL HOUSEHOLDS IN KOGI STATE, NIGERIA - Akomolafe, S.K.; Alfred, S.D. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the utilization pattern of non-timber forest products by rural households in Kogi State, Nigeria. The objective of the study was ascertain the socio-economic characteristics of the respondents and utilization pattern of NTFPs in the study areas. Multi-stage sampling procedure was used to select sixty respondents for the study. Descriptive statistics such as frequency, percentage and mean were used to analyzed the data that were gathered for this study. Most respondents were within the age group of 47 to 57 years (51.7%), followed by 36 to 46 years age group (26.7%). The respondents were still in their active and productive ages with larger percentage of them having one form of education or the other. The NTFPS collected by the respondents in the study area were fuel wood (mean=2.93), tree poles and Bamboo (mean=2.92 respectively), and medicinal plants (mean=2.88) had high utilization pattern in the study area. The study concluded that fuelwood, seasonal vegetables, medicinal plants and bamboo among others were the major NTFPs in the study area. It also concluded that the usage pattern of these NTFPs were high, this could enhance food security and sustainable livelihood in the study area. The study recommended that stakeholders and policymakers should consider NTFP sector in forest conservation measures that could meet the needs of forest-dependent communities.